Persepsi Mahasiswa Peserta Studi Independen PT. Semesta Integrasi Digital terhadap Pengembangan Kompetensi Diri di Program MBKM - Julioko Fahriza (Universitas Muhammadiyah Surakarta, 2025)
Merdeka Belajar Kampus Merdeka (MBKM) Program is designed to develop students skills and competencies. This article aims to analyze the development of self-competence within the MBKM program based on the perceptions of students participating in the Independent Study on Data. This study employs a qualitative descriptive research method. Data collection was carried out through questionnaires distributed via Google Forms to students in the Independent Study program, with a total of 31 respondents. Data were gathered through interviews, observations, and documents. Data processing was conducted using the qualitative analysis method by Miles and Huberman, which involves data reduction, data presentation, and data interpretation. The findings of this research indicate that the MBKM program is an effective effort to enhance students self-competence